Assessment of dried blood samples as an alternative less invasive method for detection of Hepatitis E virus marker in an outbreak setting. Issue 4 (30th December 2013) - Singh, Mini P.; Majumdar, Manasi; Budhathoki, Bimal; Goyal, Kapil; Chawla, Yogesh; Ratho, Radha K.
<x xml:space="preserve">Abstract</x> Hepatitis E virus (HEV) is the causative agent of hepatitis E. It can be asymptomatic, associated with acute self‐limiting hepatitis or acute liver failure. The conventional diagnosis of HEV infection relies on anti‐HEV IgM serology. The collection of blood samples by venepunture for laboratory confirmation is often difficult during an outbreak. Thus, testing the specimens of dried blood spots (DBS) on filter papers can prove to be a feasible alternative. The present study aimed to evaluate the applicability of anti‐HEV IgM detection from DBS samples and the stability of anti‐HEV IgM detection at varied time interval, at various storage temperatures. Paired blood and DBS sample were collected from 44 jaundiced patients and eight healthy controls during HEV outbreaks. The DBS were tested for anti‐HEV IgM by available ELISA kit with in‐house modifications. Three cut offs were determined, that is, the CO1: kit cut‐off, CO2: mean of negative controls above 3SD and CO3: area under Receiver operating Curve. The sensitivity of anti‐HEV IgM detection ranged from 86–91%. The maximum sensitivity (91%) and specificity (100%) was obtained using CO3. Maximum stability of anti‐HEV IgM antibodies (100%) was observed till 65 days at 4°C. Storage at 37°C significantly reduced anti‐HEV IgM positivity, wherein 42.85% sample became negative by 45 days. DBS showed good sensitivity and specificity for detecting anti‐HEV IgM and can be considered an alternate to serum sample. Moreover, anti‐HEV IgM was stable at 4°C, which makes DBS a preferred method for storage and transportation of the sample to reference laboratory. J. Med. Virol. 86:713–719, 2014. © 2013 Wiley Periodicals, Inc.